From the “White Lily” to the “King Frog in a Puddle”: A Comparison of Confederation and Multiculturalism in Irish-Canadian Literature - Urschel, Katrin (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d’études canadiennes, 2011)
The Confederating period of the 1850s and 1860s and the adoption of official multiculturalism in the 1970s are arguably two of the most decisive ideological moments in Canadian history. The literature produced during the Confederating period and the early years of multiculturalism therefore constitutes a valuable medium to discern what is at stake in reinforcing “national” and “ethnic” identities as normative categories. This paper focuses on Canadian literature written during these times by Irish Catholic immigrants and their descendants because the conflicting role of the Irish as both colonizers and colonized adds political dynamics, the explorations of which help to illustrate the objectives and shortcomings of national and multicultural ideologies. The essay analyses ideas about nation building, ethnic identity, racial supremacy, and cultural diversity in the poetry of Thomas D’Arcy McGee and Rosanna Leprohon, as well as novels by Harry J. Boyle and Dennis T. Patrick Sears.